Effect of Balloon‐Expandable Transcatheter Aortic Valve Replacement Positioning: A Patient‐Specific Numerical Model. Issue 12 (December 2016) - Bianchi, Matteo; Marom, Gil; Ghosh, Ram P.; Fernandez, Harold A.; Taylor, James R.; Slepian, Marvin J.; Bluestein, Danny
Abstract: Transcatheter aortic valve replacement (TAVR) has emerged as a life‐saving and effective alternative to surgical valve replacement in high‐risk, elderly patients with severe calcific aortic stenosis. Despite its early promise, certain limitations and adverse events, such as suboptimal placement and valve migration, have been reported. In the present study, it was aimed to evaluate the effect of various TAVR deployment locations on the procedural outcome by assessing the risk for valve migration. The deployment of a balloon‐expandable Edwards SAPIEN valve was simulated via finite element analysis in a patient‐specific calcified aortic root, which was reconstructed from CT scans of a retrospective case of valve migration. The deployment location was parametrized in three configurations and the anchorage was quantitatively assessed based on the contact between the stent and the native valve during the deployment and recoil phases. The proximal deployment led to lower contact area between the native leaflets and the stent which poses higher risk for valve migration. The distal and midway positions resulted in comparable outcomes, with the former providing a slightly better anchorage. The approach presented might be used as a predictive tool for procedural planning in order to prevent prosthesis migration and achieve better clinical outcomes.